Analisis Peluang Siaran Jambi TV di Era Industri 5.0 - Maulana, Arif; Setiawan, Ahmadi; Fabri, Erlinda Aidil; Yunita, Nurma; Khoiri, Umul (Al-Hayat: Natural Sciences, Health & Environment Journal, 2024)
Jambi TV is a television station that plays a vital role in the broadcasting media in the Jambi Province, Indonesia. Various aspects of Jambi TV include different elements that influence its operations and contributions in providing information, entertainment, and services to the people of Jambi. This writing will discuss several key aspects related to Jambi TV, including the station's profile, flagship programs, contributions in broadcasting news and information, as well as its social impact on the local community. Additionally, this report will also address the trends and challenges faced by Jambi TV in the current era of Industry 5.0, and its strategic role in meeting the audience's needs in the Jambi region. By gaining a deeper understanding of the general aspects of Jambi TV, we can appreciate its important role in regional broadcasting and its impact on the local community.